Aboard the Titanic - Son, John (New York : Children's Press, an imprint of Scholastic, Inc., 2023)
Young readers rediscover the story of the largest and most luxurious ship ever built, The Titanic. Featuring historical imagery, first-hand accounts, and text.
Introduction: All Aboard! -- First-class passengers: how did the rich and famous travel on board the Titanic? -- Second-class passengers: what type of people traveled in second class? -- Third-class passengers: what was it like to travel in steerage? -- The big truth: by the numbers : which passengers had the best chance of survival? -- All hands on deck: what jobs did crew members have on board the Titanic?
Includes bibliographical references (page 45) and index.
6.2
3-6
940L
Keywords: Titanic (Steamship) -- Juvenile literature; Titanic (Steamship) -- Employees -- Juvenile literature; Ocean travel -- Juvenile literature; Ocean liner passengers -- North Atlantic Ocean -- Juvenile literature; Shipwrecks -- North Atlantic Ocean -- Juvenile literature; Shipwreck victims -- Juvenile literature; Titanic (Steamship); Titanic (Steamship) -- Employees; Ocean travel; Ocean liner passengers; Shipwrecks -- North Atlantic Ocean; Shipwreck victims